ADOPSI POLA PUISI ARAB JAHILI DALAM AL-QUR’AN (PENDEKATAN ILMU AL-‘ARŪḌ) - Patah, Akhmad (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
In the Qur'an, there are many verses which employ one of the 16 patterns of the classical Arabic poetry metres, which in ‘Aruḍ are called baḥr (plural: buḥūr). All the patterns of the metres are applied in the Qur'an. However, these patterns are not put into practice consistently, and this inconsistency becomes the peculiarity of the Qur'an that distinguishes it from poetry. This paper specifically discusses the verses that applied the patterns as well as the specificity. Utilizing the scientific approach of ‘Aruḍ, this paper shows that although the Qur'an adopts the patterns of the poetry metres, there are at least three fundamental differences between the Qur'an and poetry. Therefore, the Qur'an can not be classified as poetry.